Health Educator Participation in Virtual Micro-Credentialing Increases Physical Activity in Public Health Competencies - Dysart, Anna; Balis, Laura E.; Daniels, Bryce T.; Harden, Samantha M. (Frontiers in Public Health, 2021)
Background. Physical activity is an important component of leading a healthy life. Public health is one of the nine major sectors for disseminating information about physical activity and increasing the physical activity of the general public. Purpose. Increase competency among Cooperative Extension agents (i.e., public health workers) on selecting, delivering, and evaluating physical activity programs through a theory-based online training program. Methods. Cooperative Extension agents from two states were invited to participate via statewide listservs. Participants were invited to attend sessions, complete competency checks and between-session assignments each week. The study was conducted using a video conferencing platform. The intervention was nine weeks from June-July 2020 and had 130 participants. Pre and post- program surveys included physical activity competencies and validated scales for flourishing and physical activity status. Data for competencies pre and post were analyzed using the Wilcoxon signed rank test, p<.01. Physical activity and flourishing pre and post were compared using t-tests, p<.05. Results. Physical activity for public health professionals competency increased significantly (p<.00) as did agents’ personal physical activity levels (p<0.05). Changes in flourishing were not significant (p<.088) but trended in the hypothesized direction. Conclusions. The online competency-based training program significantly improved Cooperative Extension agents’ knowledge of physical activity guidelines and physical activity program implementation. Future work is needed related to the scalability of the training program.